Students' guidance needs in barangay high schools in the Division of Zamboanga del Norte as perceived by administrators, teachers, and students - Ratificar, Victoria P. Cabanog (1980)
This study determined the students' guidance needs in twelve barangay high schools in the Division of Zamboanga del Norte through a survey using the Manila Counseling Inventory. The relationship in the perceptions of student needs among administrators, teachers and students, and the relationship among the perceived needs of students in the 12 schools were also considered. The results of the study showed that there was a significant relationship in the perception of students' guidance needs among the schools under study. There was also a relationship in the perceptions of students' guidance needs among administrators, teachers and students. Results of the study justified the organization of a guidance program for barangay high school students to assist them in their personality development.
Appendices: leaves 130-269
Mimeographed.
Thesis (M.Ed.)--University of the Philippines, Quezon City
Vita
Keywords: Personnel service in education -- Philippines -- Zamboanga del Norte